2004
DOI: 10.1093/treephys/24.7.775
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, morphological and allocational plasticity in understory deciduous trees: importance of plant size and light availability

Abstract: In a 4-year study, we investigated changes in leaf physiology, crown morphology and whole-tree biomass allocation in seedlings and saplings of shade-tolerant sugar maple (Acer saccharum Marsh.) and intermediate shade-tolerant yellow birch (Betula alleghaniensis Britt.) growing in natural understory light (0.5 to 35% of full sunlight) or in understory light reduced by 50% with shade nets to simulate the effect of gap closure. Leaf physiological parameters were mainly influenced by the light gradient, whereas cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 45 publications
12
143
2
6
Order By: Relevance
“…Furthermore, both Delagrange et al (2004) and Claveau et al (2005) found that the effects of tree size varied according to the availability of resource, in this case light. In the present study, most allocational ratios were strongly influenced by tree size.…”
Section: Structural and Allocational Differences Among Tropical Tree mentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, both Delagrange et al (2004) and Claveau et al (2005) found that the effects of tree size varied according to the availability of resource, in this case light. In the present study, most allocational ratios were strongly influenced by tree size.…”
Section: Structural and Allocational Differences Among Tropical Tree mentioning
confidence: 97%
“…Efforts have also been made to relate architectural characteristics to ecological characteristics (Kohyama and Hotta 1990;Coomes and Grubb 1998). For example, it is well known that early-successional species tend to increase their allocation to height growth when growing in shade (Takahashi et al 2001;Sterck 1999;King et al 1997), while late-successional ones tend to reduce or even stop their height growth in order to maintain high LWR and LAR and minimise construction costs in light-limited environments (Takahashi et al 2001;Sterck 1999;King et al 1997;Delagrange et al 2004). Biomass allocation in trees thus appears to be relatively plastic.…”
Section: Structural and Allocational Differences Among Tropical Tree mentioning
confidence: 99%
See 2 more Smart Citations
“…For Crown H/D and all traits dealing with biomass partitioning in contrasting tree compartment, ANCOVA was performed using main stem length as the covariate. This procedure was used because recent studies have highlighted the importance of individual size or height in the variation of these parameters [12,16]; such analyses allowed us to determine if trait differences between light regimes were either light-or size-induced.…”
Section: Statistical Analysesmentioning
confidence: 99%